Optimal target blood pressure for the primary prevention of hemorrhagic stroke: a nationwide observational study - Shim, Hwan Seok; Park, Jeong-Mee; Lee, Yong Jae; Kim, Young-Deok; Kim, Tackeun; Ban, Seung Pil; Bang, Jae Seung; Kwon, O-Ki; Oh, Chang Wan; Lee, Si Un (Frontiers in Neurology, 2023)
Background There are few reports on the preventative value of intensive blood pressure (BP) management for stroke, especially hemorrhagic stroke (HS), after new criteria for hypertension (HTN) were announced by the American College of Cardiology/American Heart Association in 2017. Aims This study aimed to identify the optimal BP for the primary prevention of HS in a healthy population aged between 20 and 65 years. Methods We conducted a 10-year observational study on the risk of HS, subclassified as intracerebral hemorrhage (ICH) and subarachnoid hemorrhage (SAH) according to BP categories (e.g., low normal BP, high normal BP, elevated BP, stage 1 HTN, and stage 2 HTN) using the National Health Insurance Service Database. Results Out of 8,327,751 participants who underwent a health checkup in 2008, 949,550 were included in this study and observed from 2009 to 2018. The risk of ICH was significantly increased in men with stage 2 HTN {adjusted hazard ratio [aHR] 2.002 [95% confidence interval (CI) 1.203–3.332]} and in women with stage 1 HTN [aHR 2.021 (95% CI, 1.251–3.263)]. The risk of SAH was significantly increased in both men [aHR 1.637 (95% CI, 1.066–2.514)] and women [aHR 4.217 (95% CI, 2.648–6.715)] with stage 1 HTN. Additionally, the risk of HS was significantly increased in men with stage 2 HTN [aHR 3.034 (95% CI, 2.161–4.260)] and in women with stage 1 HTN [aHR 2.976 (95% CI, 2.222–3.986)]. Conclusion To prevent primary HS, including ICH and SAH, BP management is recommended for adults under the age of 65 years with stage 1 HTN.